Problematika Implementasi Kurikulum Merdeka Di MTsN 1 Medan - Ginting, Siti Masyitah; Pohan, Selamat (Yayasan Rahmat Islamiyah, 2024)
The Independent Curriculum is one of the government's efforts to improve human resources through education. This research aims to analyze the problems of implementing the Independent Curriculum at MTsN 1 Medan. To find out this problem, the author uses a qualitative approach with a descriptive type. Data collection was carried out through interviews, observation and documentation. To analyze the data, the author uses qualitative descriptive analysis, namely processing data and describing situations according to the results of observations, interviews and documentation. The subject studied was the Deputy Principal for Curriculum at MTsN 1 Medan. The obstacles found include the diversity of student characteristics, low motivation, limited infrastructure, difficulty carrying out assessments, teacher workload, and limited learning time.